Better than normal : how what makes you different makes you exceptional - Archer, Dale (Crown Archetype, 2012)
Psychiatrist Dr. Dale Archer believes that labels for behavior like "ADHD," "bipolar," and "OCD" are normal human qualities--and contends that we all experience these and other psychological traits to some extent, yet fail to leverage the significant advantages they can offer. Here, Dr. Archer offers a framework for redefining what constitutes mental health. Drawing on his twenty years of clinical experience, he describes eight traits of human behavior. Each of these occurs along a continuum rather than as a simple on-off switch (where "off " means we're fine, and "on" means we've got a problem). These are the aspects of our personality that we worry about the most, but these are also the very things that make us distinctive and different.--From publisher description.